Penerapan Media Boneka dan Karpet Interaktif (PETRA dan PITRI) dalam Edukasi Gizi bagi Anak PAUD At-Tauhid Palembang - Arie Kusumaningrum; Anita Kristi; Nadira Andika Oktaviani; Rifda Dya A Shilla; R.A. Salsabila Aprilia; Masayu Fuja Nandini (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2026)
Background: Early childhood nutrition education is crucial in preventing nutrition-related issues such as stunting and obesity. Children at this age need a solid understanding of healthy eating to ensure optimal growth and development. An engaging and interactive approach can enhance their understanding of nutrition. Methods: This Community Service Activity was conducted at PAUD At-Tauhid in Palembang, incorporating an interactive approach using PETRA and PITRI Media. The activities included anthropometric measurements to assess children's nutritional status, storytelling sessions using PETRA and PITRI puppets, and educational games through the PETRA Interactive Carpet. This approach adopted Project-Based Learning (PJBL), allowing children to actively participate in the learning process. Results: Nutritional status measurements showed that most children had good nutritional status, though some were at risk of being overweight or obese. Storytelling sessions with the PETRA and PITRI puppets revealed that 95% of the children could correctly identify healthy and unhealthy foods. The PETRA Interactive Carpet game successfully engaged 95% of the children, reflecting the success of the PJBL approach in enhancing children's knowledge and skills regarding nutrition. Conclusion: The innovative healthy food education through the interactive approach using PETRA and PITRI proved effective in introducing the concept of healthy eating in a fun and applicable way for early childhood. This approach can serve as a model to be applied in other PAUD centers to improve children's nutritional understanding and prevent future nutrition-related issues. Keywords: Nutrition Education, PETRA, PITRI, Interactive Carpet, Early Childhood, Nutrition, Gamification, Storytelling.